1974
DOI: 10.1113/expphysiol.1974.sp002255
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein Bound Iron in the Blood Plasma of the Laying Hen

Abstract: 1. Plasma iron in the laying hen has been separated into two components by adsorption on magnesium carbonate, gel filtration and ion exchange chromatography. 2. The non‐transferrin component is closely associated with phosphoprotein. 3. There is no exchange of iron in vitro between the components, but in the living bird transferrin iron seems to be the precursor of the phosphoprotein iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…5). Iron exchange between transferrin and phosvitin did not occur during in vitro incubation of plasma, as has also been demonstrated by Ali and Ramsay [1974]. Since phosvitin is synthesized in the liver there can be little doubt that the metabolic pathway of iron in laying or oestrogen treated birds is from plasma transferrin to liver cells where it is incorporated into phosvitin which is in turn secreted into the plasma.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…5). Iron exchange between transferrin and phosvitin did not occur during in vitro incubation of plasma, as has also been demonstrated by Ali and Ramsay [1974]. Since phosvitin is synthesized in the liver there can be little doubt that the metabolic pathway of iron in laying or oestrogen treated birds is from plasma transferrin to liver cells where it is incorporated into phosvitin which is in turn secreted into the plasma.…”
Section: Discussionmentioning
confidence: 60%
“…1) and iron or radioactive iron on transferrin should be well separated from that of phosvitin by gel filtration on Sephadex G150 or G200. This was found to be the case by Ali and Ramsay [1974] who provided evidence from ion-exchange chromatography that the iron in the fractions which eluted at the void volume was present as a phosphoprotein, almost certainly phosvitin.…”
Section: Plasma Fractionation Techniquesmentioning
confidence: 75%
See 1 more Smart Citation
“…Under normal physiological conditions, lactoferrin is present at very low plasma concentrations and is not considered to play any significant role in j ron trùnsport (Morgan, 1981 ovotransfprrin, found in bird yolk sac, is also known to bjnd iron but only in a bacteriostatic capacity. Finally vitellogenin, which is not known to be expressed in mammals (Ali andRamsay, 1974~ Morgan, 1975) has been shown ta have ùn iron-transport role in birds, fish and sorne reptiles (Wallace and Bergink, 1974;Dessauer, 1974;Craik, 1978 (Bergeron, 1986). This is evidenced by a vital role in biological redox reactions, serving as the prosthetic group in cytochrornes, catalases, as cofactor of ribonucieotide reductase, a rate-limiting enzyme in DNA synthesis etc.…”
Section: -'mentioning
confidence: 99%
“…Early studies (Ramsay and Campbell, 1954) showed that the laying process affected iron metabolism and that oestrogens are important mediators in this process (Ramsay and Campbell, 1956;Planas and Frieden, 1973;Morgan, 1975;LopezBerjes et al, 1981). The mobilisation of iron increases the plasma iron transport capacity (Planas et al, 1961;Ali and Ramsay, 1974;Morgan, 1975;Lopez-Berjes et ah, 1981) and the egg yolk and the erythropoietic organs are its main destinations (Halkett et al, 1958;Planas and Balasch, 1970;Morgan, 1975;Marti et al, 1989a). Thus, during the laying state, a significant increase in plasma iron turnover was observed in the different species analysed (chick-339 ens, ducks, turkeys) (Planas and Balasch, 1970;Balasch and Planas, 1972).…”
Section: Introductionmentioning
confidence: 99%